Penerapan Metode Talaqqi dan Metode Muraja’ah Dalam Meningkatkan Hafalan Al-Qur’an di SDQU Darul Fatah Pangkalpinang - Rudini, Rudini; Doni, Doni (LENTERNAL: Learning and Teaching Journal, 2023)
This research problem is motivated by the application of the Talaqqi method and the Muraja'ah method in the Qur'an tahfidz program. The Talaqqi and Muraja'ah methods make it easier for ustadz or ustadzah to choose the right way to recite the Qur'an as well as motivate students to quickly complete memorization. This research was conducted to explain: (1) how the application of the talaqqi method and themuraja'ah method in learning the Qur'an tahfidz at SDQU Darul Fatah Pangkalpinang. (2) how are the constraints in the application of the Talaqqi Method and theMuraja'ah method in learning the Qur'an Tahfidz at SDQU Darul Fatah Pangkalpinang. This research uses qualitative research, namely by describing data in the form of directed and systematic words. The data sources in this study are supervisors (musyrif) and students as primary data sources. Data collection techniques are carried out with interviews, observations, and documentation. Data analysis techniques are carried out by managing or simplifying the collected data, from the simplification of the data, analysis is carried out and then conclusions are drawn. The results showed that the application of the Talaqqi method was carried out in several ways, namely Improving (rawsin) reading students, depositing (mentasmi') new memorization (sabaq), and exams every time one juz of new memorization was completed. The application of the Muraja'ah method is carried out in two ways, namely muraja'ah new memorization (sabqi), muraja'ah memorization old (manzil). The constraint factor is that it is inefficient when facing more than 15 students, and lies in the learners themselves, be it in the pronunciation of the makharijul letters, the nature of the letters, the short length (mad), and the law of tajwid. The solution is by multiplying the human resources of Qur'an experts, coaching to supervisors (musyrif), providing motivation to each student, and collaborating with parents of students.